Factors of Poor Adherence Among Adolescents Living With Hiv/aids in Nsambya Home Care. - Halima Noel Julie Lurit (Uganda Christian University, 2024)
This study was based on the factors of poor adherence among adolescents in Nsambya home care. A content analysis of secondary data where social work articles and social work journals were used to collect and analyze data. The study findings indicate that the adolescents undergo multifaceted challenges which were categorized into interpersonal factors such forgetting to take HIV medication, medication side effects, lack of food and institutional factors were less HIV counselling and also stigma from community traumatized and affected the way adolescents adhere to medication. The study shows the different challenges such neglect, abuse and other psycho-social factors where by social workers are ill-equipped to handle the psycho-social needs of the adolescents which has led to poor adherence among the adolescents. Possible strategies were also identified in the study to be able to improve the quality of life of the adolescents such use of interactive voice response to make pill reminders and social worker€s role of providing counseling and educating adolescents about positive living. In conclusion, the study demonstrates the multifaceted challenges adolescents face which leads to poor adherence, social worker€s role and possible strategies which can be used to improve the quality of life and wellbeing of the adolescents in the adolescent peer center program in Nsambya home care.